Characteristics of Professional Liability Insurance for Doctors in Indonesia - I Putu Gde Budhi Setiawan; Mokhamad Khoirul Huda (Faculty of Law Universitas Jenderal Soedirman, 2025)
Regulation of the Minister of Health of the Republic of Indonesia Number 755/MENKES/PER/IV/2011 concerning the Organization of Medical Committees in Hospitals in the section on credential mechanisms and granting of clinical authority for medical personnel in Hospitals in number 12 point D states that: